2018
DOI: 10.15294/dp.v13i2.17051
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Entrepreneurial Intention Through Behavioral Approaches

Abstract: The purpose of this study was to determine the effect of entrepreneurial attitudes, subjective norms and perceived behaviour control on entrepreneurial intentions both directly and indirectly and to know the differences in entrepreneurial intentions in terms of gender, regional origin, and scientific fields. The research method used was explanatory survey method. The population was 19,919 students with a sample size of 377 respondents. The research sample taken from the UPI student population consisted of 13 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
1
0
3
Order By: Relevance
“…It came out from the study that PBC show a significant influence on students' entrepreneurial intention. This is consistent with the empirical studies of Abubakar et al, 2019;Kurjono et al, 2018;Jonanov et al, 2021.…”
Section: Perceived Behavioural Control and Student's Entrepreneurial ...supporting
confidence: 92%
“…It came out from the study that PBC show a significant influence on students' entrepreneurial intention. This is consistent with the empirical studies of Abubakar et al, 2019;Kurjono et al, 2018;Jonanov et al, 2021.…”
Section: Perceived Behavioural Control and Student's Entrepreneurial ...supporting
confidence: 92%
“…Through Planned Behavior Theory (PBT), it states that intentions are explained through behavioral attitudes, subjective norms, and perceived behavioral control (Kurjono, 2018). Based on this it can be concluded that one's intention to set up their own business may be a strong attitude towards entrepreneurial development (Gochhait, 2020).…”
mentioning
confidence: 99%
“…Seorang pengusaha yang memiliki kemampuan mengelola keuangan usahanya akan semakin tinggi tingkat intensi wirausahanya. Sebagaimana dijelaskan oleh Kurjono et al (2018), bahwa ketika seseorang memilih menjadi wirausaha maka harus mempunyai intensi wirausaha yang tinggi yang dibentuk dari kemampuan baik secara finansial maupun manajerial. Hasil penelitian ini menjelaskan bahwa apabila mahasiswa memiliki kemampuan yang baik dalam mengelola keuangan usahanya, maka tingkat intensi wirausahanya akan semakin tinggi.…”
Section: Pengaruh Manajemen Keuangan Terhadap Intensi Mahasiswa Pmw U...unclassified
“…Walaupun negara lain mempunyai rasio lebih tinggi, contohnya Amerika Serikat dengan rasio 12%, Jepang dengan rasio 11%, Singapura dengan rasio 7% dan Malaysia dengan rasio 5% (Kemenkop dan UKM, 2020). Sebagaimana pendapat Kurjono et al (2018) ketika seseorang memilih menjadi wirausaha maka dia telah memiliki intensi wirausaha yang tinggi. Namun tidak semua orang yang memiliki niat wirausaha mampu mewujudkan niat tersebut (intensi).…”
unclassified